Perancangan Sistem Informasi Akuntansi Penerimaan Kas (Studi Kasus : Koperasi Kota Salatiga) - Mery Rizky Aryanti; Purwanto -; Suharyadi - (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2019)
The development of information technology provides quite influential benefits from all fields, both in education, health, economics and so on. Organizations can utilize the development of information technology to process data, including processing, obtaining, compiling, and storing data to produce quality information. The study was conducted at the fostered cooperatives of the Salatiga City Cooperative Office. The author's research objective is to analyze the data needed for the Salatiga Cooperative Cash Receipt Accounting Information System, to design the Salatiga Cooperative Cash Receipt Accounting Information System. The discussion includes: 1. Analysis of the accounting system for cash income. 2. Requirements needed for accounting information systems for cash income. 3. Designing an accounting system for cash income. 4. Implementation, testing and analysis of cash income accounting information systems. The Salatiga Cooperative Cash receiving system was designed using the PHP web format and using MySQL. Design of Accounting Information System for Salatiga Cooperative Cash Income includes Data Flow Diagrams (DFD), Use Case Diagrams, Entity Relations Diagrams (ERD), tables such as user tables, company profile tables, transaction tables, journal tables, master tables, calculation report tables business, balance sheet report table and forms used in the system. The Accounting Information System for Salatiga Cooperative Cash Receipts responds to the department's need for Financial Statements from each cooperated cooperative every 3 months and / or once a year, Reports with the same format, Balance Reports.